Exposição crônica ao herbicida paraquat promove desequilíbrio no sistema antioxidante e alterações comportamentais em peixe zebra (Danio rerio) - Nunes, Mauro Eugênio Medina (2015)
In the last decade, it has been investigated behavioral patterns that may to reflect the physiological and biochemical changes in promising experimental models. Zebrafish (Danio rerio) is an useful tool for studying dose-response effects when exposed to contaminants and biomonitoring studies. The exposure to herbicide paraquat (PQ), a common environmental contaminant, is considered a risk factor for the development of neurodegenerative diseases such as Parkinson's disease. In the brain the PQ acts on the dopaminergic neurons by inducing a state of oxidative stress through its redox cycle on the nicotinamide adenine dinucleotide phosphate (NADPH) and also on the mitochondria, leading mitochondrial dysfunction and death of these neurons. Thus, the aim of this study was to evaluate behavioral parameters and biochemical changes in zebrafish brain chronically treated PQ. PQ (20 mg/kg; treated group) or saline (0.9%; control group) were administrated intraperitoneally, one injection every 3 days for 16 days totalized six injections in adult zebrafish of both sexes. Zebrafish treated with PQ showed a less anxious character in relation to control group, due the decrease in defense behaviors, such as time spend in bottom section, latency to first entry to upper section and number and duration of risk assessment episodes in novel tank and light-dark test. Additionally, treated animals showed a more aggressive character, increasing the time and duration of the aggressive episodes in the inclined mirror-image stimulus. However, alterations in locomotor and motor patterns were not observed. In addition, PQ induced brain damage due decrease of ± 10% of the mitochondrial viability. Treatment with PQ also induced the increase of antioxidant defense system activity, as biomarkers catalase (CAT) glutathione peroxidase (GPx), and non-protein thiols (NPSH) levels, as well as the glutathione-S-transferase (GST). However, there were no changes in the levels of reactive oxygen species (ROS) and oxidative damage in lipids (TBARS). We demonstrated for the first time that PQ induced an increase in aggressive behavior, decreasing non-motors patterns associated to defense behaviors. We suggest that fish exposed to PQ are more susceptible to predation, since it seems to be more exposed to danger. The increase in aggression can influence the social behavior of the fish group. Behavioral changes may be associated to brain damage observed by decreased mitochondrial viability in zebrafish brain.